2019
DOI: 10.1177/1099800419861695
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nocturnal Sleep Quality on Diurnal Cortisol Profiles and Attention in Nurses: A Cross-Sectional Study

Abstract: Objective: Low sleep quality (LSQ) activates the hypothalamic–pituitary–adrenal (HPA) axis and is related to arousal. Nursing staff, who work in shifts, tend to exhibit LSQ, which affects the level of vigor after awakening. This study investigated the effects of nocturnal sleep quality on diurnal cortisol profiles and sustained attention in day-shift nurses. Method: This study adopted a prospective cross-sectional design. Participants were recruited from a university-affiliated hospital in northern Taiwan. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…In physiological circumstances, cortisol levels are elevated in the morning, according to the findings of this study, in which 10.7% of nurses had peak secretion upon awakening, however with values above the reference, which may be indicative of some sleep disorder (30) . Studies have identified that increased cortisol secretion may indicate occupational stress chronification (14,31) with greater activation of the HPA axis (29) , and that, in chronic stress, atypical patterns of cortisol secretion may occur, as the flat pattern, in which the secretion of this hormone remains high during the day (14) .…”
Section: Discussionsupporting
confidence: 60%
“…In physiological circumstances, cortisol levels are elevated in the morning, according to the findings of this study, in which 10.7% of nurses had peak secretion upon awakening, however with values above the reference, which may be indicative of some sleep disorder (30) . Studies have identified that increased cortisol secretion may indicate occupational stress chronification (14,31) with greater activation of the HPA axis (29) , and that, in chronic stress, atypical patterns of cortisol secretion may occur, as the flat pattern, in which the secretion of this hormone remains high during the day (14) .…”
Section: Discussionsupporting
confidence: 60%
“…Irregular shift work causes nurses' biological clocks to be disturbed, causing the body and mind to be in a state of stress, making them prone to shift work disorder, which is mainly manifested as insomnia and drowsiness (Ai & Guan, 2015). It had also been pointed out that shift nurses tend to show low sleep quality, which has been shown to activate the hypothalamic-pituitary-adrenal axis and was related to sleep arousal (Tsai, Chou, Tsai, Yen, & Niu, 2019). Previous research has shown that more than 5 night shifts per month and long working hours will seriously affect sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Each item has four possible answers (never = 0, sometimes = 1, generally = 2, and always = 3). Total scores are then classified into four groups: non-emotional eater (0-5), low emotional eater (6-10), emotional eater (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and very emotional eater (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). To analyze factor structure and psychometric properties of Emotional Eater Questionnaire (EEQ), the authors recruited 295 participants, and Exploratory Factor Analysis (EFA) was carried out by using the Unweight Least Squares (ULS) method [41].…”
Section: Instrumentsmentioning
confidence: 99%
“…Change in eating habits was another common coping mechanism for nurses; this could be in the form of consuming high energy-dense foods that have a significant correlation with weight gain [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%